PELAKSANAAN TANGGUNG JAWAB PENGANGKUT UDARA TERHADAP KEHILANGAN BAGASI TERCATAT - Khairunnisa, Tri Rahmi; Bachtiar, Maryati; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Reciprocal relationship between the air carrier in this case PT. Lion Air Office Pekanbaru and passengers as service users created rights and obligations of each party. However, in practice lost baggage that causes damage to passengers without the fulfillment of the rights of passengers as appropriate The purpose of this study, to investigate the implementation of the air carrier liability for lost baggage on the PT. Lion Air Representative Office Pekanbaru, to find remedies that can be taken by a passenger to lose baggage at. Lion Air Office Pekanbaru This type of research is a sociological study, because in this study the authors directly conduct research on the location or place under study in order to provide a complete and clear picture of the problem under study. This research was conducted at PT. Lion Air Office Pekanbaru, while the population and the sample is a whole party relating to the issues examined in this penelitiaan, data source used, primary data, secondary data and data tertiary, data collection techniques in this study with interviews, filling the questionnaire, and literature. Implementation responsibilities lost baggage by PT. Lion Air Office Pekanbaru based on the presumption of innocence which responsibilities according to this concept the air carrier was found guilty and will pay compensation for the loss of checked baggage. Remedy which can be carried by the passenger is through non-litigation and litigation provisions are based on legislation. To the PT. Lion Air Pekanbaru Representative Office in order to further improve the monitoring of goods baggage belonging to passengers and provide transparency of procedures regarding the efforts that can be taken by passengers in the event of loss of baggage. To the government in order to further improve the oversight of the air carrier to provide legal protection and guarantees the fulfillment of the right of every citizen. To the passenger so valuable luggage reported to the clerk at check-in, or valuable items should be placed on cabin baggage.Keywords: Responsibility - Carrier - Checked Baggage